Contractualism, Person-Affecting Wrongness and the Non-identity Problem - Katz, Corey (Ethical theory and moral practice, 2018)
A number of theorists have argued that Scanlon's contractualist theory both "gets around" and "solves" the non-identity problem. They argue that it gets around the problem because hypothetical deliberation on general moral principles excludes the considerations that lead to the problem. They argue that it solves the problem because violating a contractualist moral principle in one's treatment of another wrongs that particular other, grounding a person-affecting moral claim. In this paper, I agree with the first claim but note that all it shows is that the act is impersonally wrong. I then dispute the second claim. On Scanlon's contractualist view, one wrongs a particular other if one treats the other in a way that is unjustifiable to that other on reasons she could not reasonably reject. We should think of person-affecting wronging in terms of the reasons had by the actual agent and the actual person affected by the agent's action. In non-identity cases, interpersonal justifiability is therefore shaped both by the reason to reject the treatment provided by the bad suffered and the reason to affirm the treatment provided by the goods had as a result of existing. I argue it would be reasonable for the actual person to find the treatment justifiable, and so I conclude that Scanlon's contractualist metaethics does not provide a narrow person-affecting solution to the non-identity problem on its own terms. I conclude that the two claims represent a tension within Scanlon's contractualist theory itself.